Primary retroperitoneal müllerian adenocarcinoma: a case report - Feng, Xiaohui; Zhang, Ping; Gao, Feng (Frontiers in Oncology, 2024)
A 45-year-old woman presented with right hip pain for a month. Imaging revealed that the left peritoneal mass was accompanied by metastases of the right sciatic branch, lung, and retroperitoneal lymph nodes. A biopsy of the left peritoneal mass was performed. The pathological morphology demonstrated clear cell adenocarcinoma. Immunohistochemical staining revealed positive expression of keratin7 and PAX8, and negative expression of keratin20, GCDFP-15, ER, PR, WT1, CDX2, Villin, TTF-1, Napsin-A, Vimentin, Calretinin and GATA3. Finally, the diagnosis of primary retroperitoneal müllerian adenocarcinoma (PRMA) was confirmed. PRMA is a very rare type of primary retroperitoneal tumor. The PRMA should be considered for the retroperitoneal mass.